Reinserção no mercado de trabalho: respostas dos programas de trabalho e renda - Araújo, Carlos Campos (2008)
The present master's dissertation had the objective to analyze the types of responses the programmes of work and income, its limits and possibilities as mechanisms for reintegration of unemployed in the market of work, in the city of São Paulo, between 2001 to 2006. The search started the idea that the answers are limited and palliatives front to the increase of the unemployment and the precarization of the market of work. The work was supported in bibliographical survey, of documents and empirical research with the beneficiaries of the programs, social workers and managers. The study showed that the social programs of work and income meet partially a share of the demands of work and income of a parcel of the poor population and do not guarantee the reintegration in the market of work. The types of answers were the granting of aid-money to smooth the difficulties of the population about the lack of work; responsibility of the person by their situation of unemployment, the spread of alternative forms of employment and generation of income through self - employment forms and associations of different modalities